Designs and Performance Characteristics of Coated Nanotoroid Antennas - Sami Ur Rehman; Junping Geng; Richard W. Ziolkowski; Ying Wang; Xianling Liang; Ronghong Jin (International Journal of Antennas and Propagation)
The electromagnetic properties of a toroidal coated nanoparticle (T-CNP) antenna with an active core (doped with rare earth erbium Er3+ ions) are investigated. It is demonstrated that the active T-CNP acts as a strong dipole radiator at its resonance frequency when it is excited by a plane wave or an electric Hertzian dipole (EHD) radiating element. It is shown that in comparison to being a passive structure, the plane wave scattering cross section of the T-CNP can be increased by nearly 108 dBsm at its resonance frequency when it is active. Moreover, it is further demonstrated that the maximum peak of the power radiated by an EHD element in the presence of a properly designed active T-CNP is more than 120 dB over its value when radiating in free space; that is, its Purcell factor is 1012.